2008
DOI: 10.1177/193229680800200517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Modeling, and Simulation of the Accuracy of Continuous Glucose Sensors

Abstract: Background: Continuous glucose monitors (CGMs) collect a detailed time series of consecutive observations of the underlying process of glucose fluctuations. To some extent, however, the high temporal resolution of the data is accompanied by increased probability of error in any single data point. Due to both physiological and technical reasons, the structure of these errors is complex and their analysis is not straightforward. In this article, we describe some of the methods needed to obtain a description of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 23 publications
1
136
0
4
Order By: Relevance
“…The interpretation of autocorrelation is more complex: roughly, higher autocorrelation would result in longer stretches of sensor errors in the same direction, observed for example during transient loss of sensitivity. 55 To simulate realistic CGM errors, we used 280 actual CGM traces (12 h long) compared with frequent YSI glucose analyzer measurement (every 15 min). Each trace produces a ''signature'' in term of fluctuation of the error in time (time-dependent bias, drift, delay, low-frequency fluctuations, and high-frequency variability).…”
Section: Sensor Errormentioning
confidence: 99%
“…The interpretation of autocorrelation is more complex: roughly, higher autocorrelation would result in longer stretches of sensor errors in the same direction, observed for example during transient loss of sensitivity. 55 To simulate realistic CGM errors, we used 280 actual CGM traces (12 h long) compared with frequent YSI glucose analyzer measurement (every 15 min). Each trace produces a ''signature'' in term of fluctuation of the error in time (time-dependent bias, drift, delay, low-frequency fluctuations, and high-frequency variability).…”
Section: Sensor Errormentioning
confidence: 99%
“…In 1974, Albisser, et al [15] developed the artificial pancreas, but it is only utilised for in clinical studies that time. According to Boiroux, et al [16] the time constant is related to glucose transport from blood to subcutaneous tissues was 15 min, where the parameters for the CGM model is given by Breton and Kovatchev [17]. However, this may not be accurate because the body of human still yet knows what time will respond for allowing the pancreas to give insulin.…”
Section: An Artificial Pancreasmentioning
confidence: 99%
“…Chase and colleagues, 14 after having pointed out that no studies about sensor error were previously available, proposed to model sensor errors in the simplest way, i.e., a random white noise Gaussian process with a constant coefficient of variation. Breton and Kovatchev 15 proposed a more sophisticated model, where sensor error is not white and also non-Gaussian. In particular, after analysis of a data set from 28 type 1 diabetic subjects consisting of both CGM data (1-minute sampling) and BG references measured frequently in parallel (15-minute sampling), they concluded that the time series of the reconstructed CGM sensor errors can be described as realization of the output of an autoregressive (AR) filter of order 1 driven by white noise.…”
Section: State Of the Artmentioning
confidence: 99%
“…In particular, after analysis of a data set from 28 type 1 diabetic subjects consisting of both CGM data (1-minute sampling) and BG references measured frequently in parallel (15-minute sampling), they concluded that the time series of the reconstructed CGM sensor errors can be described as realization of the output of an autoregressive (AR) filter of order 1 driven by white noise. The procedure adopted 15 included two major steps: (a) CGM data were recalibrated by fitting a linear regression model against all the available BG references 16 and (b) in order to take into account distortion due to BG-to-IG dynamics, data fit incorporated the linear time-invariant (LTI) model of BG-to-IG kinetics proposed elsewhere. 17 Notably, in step b, a "population" value of the time constant τ of the model of BG-to-IG kinetics was determined and used for all the 136 individuals of the data set.…”
Section: State Of the Artmentioning
confidence: 99%